Relationship Between Knowledge and Self-Efficacy with IUD Choice in Active Family Contract Acceptors Based on Social Cognitive Theory - Shiva Salsabillah (Faculty of Medicine, Universitas Negeri Surabaya, 2025)
The use of long-acting reversible contraceptives (LARC) such as IUDs is still low in Indonesia, especially among active contraception acceptors. One of the influencing factors is knowledge and self-efficacy. Based on social cognitive theory, a person's behavior, including choosing contraception, is influenced by personal, behavioral, and environmental factors. The purpose of this study was to determine the relationship between knowledge and self-efficacy with the choice of IUD in active contraceptive services acceptors based on social cognitive theory. This study used an observational analytical approach with a cross-sectional design. The study population consisted of 577 active contraception acceptors, and the sample consisted of 150 active contraceptive services acceptors selected by simple random sampling. The study was conducted at the Candi Sidoarjo Health Center. The independent variables in this study were knowledge and self-efficacy and the dependent variable was the choice of IUD in active contraceptive services acceptors. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis was carried out using the Spearman-rank statistical test, with α ≤ 0.05. The results of the study showed that there was a relationship between knowledge and IUD selection p-value = 0.044 (α ≤ 0.05) which had a coefficient value of r = 0.265 which means it has a moderate correlation. In addition, there was a relationship between self-efficacy and IUD selection p-value = 0.035 (α ≤ 0.05) which had a coefficient value of r = 0.232 which means it has a moderate correlation. It was concluded that knowledge and self-efficacy were related to IUD selection in active contraceptive services acceptors. This is in line with the social cognitive theory which emphasizes the influence of personal factors, so that health workers are needed to improve education about long-term contraception, especially IUDs and strengthen self-efficacy through effective counseling by health workers to contraceptive services acceptors.